A scoping review on traditional medicine for bruxism - Lin Ang; Eunhye Song; Myeong Soo Lee; Yee Ang (Journal of Traditional Chinese Medical Sciences, 2023)
Objective: To investigate the current evidence on traditional medicine in managing bruxism and its clinical efficacy. Methods: A search was conducted in nine databases to identify potential eligible articles published from the date of inception until August 3, 2022. All clinical studies that used traditional medicine of any type in treating bruxism were eligible for inclusion. Two authors performed data extraction and quality assessments independently. Retrieved data were tabulated and discussed narratively. Results: A total of 16 clinical studies were included in this scoping review. Of the 16 studies, three studies were randomized controlled trials, one was a case–control study, 10 were case series, and two were case reports. Our review identified studies of interventions based on herbal medicine and acupuncture-related therapies. Most studies reported positive results, but the overall quality of the included studies was typically fair to poor. Conclusions: This study is the first scoping review on traditional medicine for bruxism despite the limited evidence. More research on traditional medicine in bruxism management should be conducted for better clarification and application in daily practice.